Borderline Ovarian Tumor during Pregnancy: A Case Report. (10th April 2013) - Casanova, Joao; Maciel, Raquel; Ferreira, Vânia; Fernandes, Eugénia; Rodrigues, Rosa Maria
Abstract : We report a case of a 33 year-old pregnant woman who was diagnosed at the time of the first trimester ultrasound with a multilocular solid arising form the right ovary. An abdominal MRI was performed afterwards and it revealed a pelvic mass, developing from the right ovary, with a liquid component but with a major solid area. CA 125 was within the normal range values. A laparotomy followed by right salpingo-oophorectomy was performed at 14 weeks of gestation and both the frozen section and the definitive histology revealed a borderline mucinous ovarian tumor. Ovarian tumors of low malignant potential comprise 10%–20% of all ovarian malignancies. They carry an excellent prognosis with 95%–99% long-term survival. Whereas in the past, radical surgery (hysterectomy and bilateral salpingo-oophorectomy with peritoneal staging) was standard regardless of the age of the patient, unilateral salpingo-oophorectomy with or without staging has become the recommended management for women who desire childbearing. In the absence of large prospective randomized trials it is difficult to know which are the best management practices and especially to determine the right moment during pregnancy to perform surgery in these patients.